Mechanism of galanin's inhibitory action on pancreatic enzyme secretion: modulation of cholinergic transmission–studies in vivo and in vitro. Issue 11 (November 1993) - Herzig, K H; Brunke, G; Schön, I; Schäffer, M; Fölsch, U R
Abstract : This study examined the inhibitory mechanism of galanin, a 29 amino acid polypeptide on pancreatic enzyme secretion in anaesthetised rats, isolated pancreatic acini, and lobules. Urethane anaesthetised rats with pancreatic fistulas pretreated with 3-0-methyl-glucopyranose (500 mg/kg/h) were stimulated with an intravenous bolus of 2-deoxyglucose (2-DG) (75 mg/kg). Maximal amylase secretion was mean (SEM) 274 (19)% of basal secretion. Atropine (150 micrograms/kg/h) and galanin (10 nmol/kg/h) almost completely inhibited 2-DG stimulated amylase secretion suggesting an inhibition of cholinergic transmission. To further test this possibility this study investigated the effect of galanin on carbachol and cholecystokinin stimulated amylase release from isolated pancreatic acini. Galanin did not suppress carbachol or cholecystokinin stimulated amylase release, indicating that galanin inhibits exocrine secretion by indirect mechanisms. The cholinergic pathway was assessed by using pancreatic lobules containing intrapancreatic neurons. Veratridine, a sodium channel activator, dose dependently stimulated amylase release. Veratridine (100 microM) stimulated amylase release by 411 (10)% of basal secretion. Atropine (1 microM) or tetrodotoxin (1 microM) almost completely blocked veratridine stimulated amylase release. Galanin (1 microM) significantly inhibited veratridine stimulated amylase release with a maximal inhibition of 50% (p < 0.05). In addition, when lobules were incubated with [3H]-choline, galanin significantly (p < 0.05) inhibited veratridine stimulated release of newly synthesised [3H]-acetylcholine. Thus galanin inhibits pancreatic secretion by inhibiting cholinergic transmission. These studies show that galanin inhibits rat pancreatic enzyme secretion by an indirect mechanism by reducing cholinergic transmission.